2017
DOI: 10.3389/fgene.2017.00097
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Methylation-Level Assessment of Hundreds of CpG Sites by Targeted Bisulfite PCR Sequencing (TBPseq)

Abstract: Methylated-DNA sequencing technologies are producing vast amounts of methylome data from cancer samples, from which cancer-associated differentially methylated CpG sites (cDMCs) are continuously identified and filed. The inclusion of as many cDMCs as possible helps improve the accuracy of cancer diagnosis and sometimes identify cancer subtypes. However, the lack of an established method for the analysis of 100s of cDMCs practically impedes their robust use in clinical medicine. Here, we tested the availability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…As a drawback of the MBD‐seq method, it is semiquantitative in the sense that it does not yield direct estimates of CpG methylation levels. Thus, the previously suggested pipeline of methylome study (Aberg et al, ) looks relevant: MBD‐seq offers a first pass at global methylation analysis, and then, the identified genomic loci of interest are subject to a base‐level validation using technologies, such as pyrosequencing and targeted bisulfite PCR sequencing (TBP‐seq; Jeon, Min, Park, & Kang, ).…”
Section: Discussionmentioning
confidence: 99%
“…As a drawback of the MBD‐seq method, it is semiquantitative in the sense that it does not yield direct estimates of CpG methylation levels. Thus, the previously suggested pipeline of methylome study (Aberg et al, ) looks relevant: MBD‐seq offers a first pass at global methylation analysis, and then, the identified genomic loci of interest are subject to a base‐level validation using technologies, such as pyrosequencing and targeted bisulfite PCR sequencing (TBP‐seq; Jeon, Min, Park, & Kang, ).…”
Section: Discussionmentioning
confidence: 99%
“…Jeon et al . presented a targeted bisulfite PCR sequencing technology for the assessment of methylation levels of CpGs residing at promoters of cancer‐associated genes over the genome 15 . It can be observed that CpGs at LIFR gene promoter, the known hypermethylated region in CRC, were heavily methylated in colon cancer cells while it is not observable in other four types of cancer cells.…”
Section: Sequencing Methods For Dna With Different Derivationsmentioning
confidence: 99%
“…There are four widely adopted methods to characterize genome‐scale patterns of DNA methylation: (i) WGBS; (ii) Infinium HumanMethylation450 BeadChip; (iii) reduced representation bisulfite sequencing; and (iv) methylated DNA binding domain sequencing and methylation DNA immunoprecipitation sequencing 15 . Among those methods, a recent study combined methylation DNA immunoprecipitation sequencing and machine learning to detect and localize cancer tissues including CRC.…”
Section: Sequencing Methods For Dna With Different Derivationsmentioning
confidence: 99%
See 1 more Smart Citation
“…LIFR(p=4.90e-04) had 4 hit papers and encodes protein that belongs to the type I cytokine receptor family. One of the studies used the meta-analysis with public cancer methylome data verified the colon cancer specificity of LIFR promoter methylation (40). Kim et al suggested that a missense mutation of LIFR rs3729740 may be useful as a biomarker for predicting whether metastatic colorectal adenocarcinoma patients were sensitive to relevant target regimens (41).…”
Section: Genes Significant Only In An Individual Cancermentioning
confidence: 99%